2020
DOI: 10.1021/acsami.0c13066
|View full text |Cite
|
Sign up to set email alerts
|

Simple, Effective, and Ecofriendly Strategy to Inhibit Droplet Bouncing on Hydrophobic Weed Leaves

Abstract: Despite small-molecule surfactants and polymers being widely used as pesticide adjuvants to inhibit droplet bouncing and splashing, they still have intrinsic drawbacks either in the easy wind drift and evaporation, the unfavorable wettability, or the usage of nonrenewable resources. In this paper, we found that upon droplet impacting, 1D nanofibers assembled from natural glycyrrhizic acid (GL) could pin on the rough hydrophobic surface and delay the retraction rate of droplets effectively. Using GL as a tank-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 44 publications
0
32
0
Order By: Relevance
“…To date, many efforts have been devoted toward regulating droplet impact and wetting behaviors on hydrophobic surfaces by adjusting droplet properties. One of the most efficient strategies is adding surfactants due to their excellent surface activity, fast diffusion rate, accurate molecular structure, low viscosity, and favorable stability. During the impact, surfactants diffuse from the bulk to the newly generated interface, thereby reducing the surface tension and preventing the droplet from bouncing off the solid surface. For example, Mourougou-Candoni et al found that upon impacting on a low-surface-energy solid substrate, droplets containing isodecyl polyoxyethylene (C 10 OE 6 ) exhibited much slower receding compared with water droplets, which was mainly attributed to a rapid decrease in dynamic surface tension .…”
Section: Introductionmentioning
confidence: 99%
“…To date, many efforts have been devoted toward regulating droplet impact and wetting behaviors on hydrophobic surfaces by adjusting droplet properties. One of the most efficient strategies is adding surfactants due to their excellent surface activity, fast diffusion rate, accurate molecular structure, low viscosity, and favorable stability. During the impact, surfactants diffuse from the bulk to the newly generated interface, thereby reducing the surface tension and preventing the droplet from bouncing off the solid surface. For example, Mourougou-Candoni et al found that upon impacting on a low-surface-energy solid substrate, droplets containing isodecyl polyoxyethylene (C 10 OE 6 ) exhibited much slower receding compared with water droplets, which was mainly attributed to a rapid decrease in dynamic surface tension .…”
Section: Introductionmentioning
confidence: 99%
“…To further understand and characterize the impact dynamics of droplets on the surface of powdery mildew, we used the widely applied normalized maximum contact diameter D t / D 0 and bounce height H t / D 0 , , where D 0 represents the initial radius of droplets, D t is the contact spreading diameter, and H t denotes the distance between the top of the droplet and the surface of the powdery mildew leaf. Figure shows that the changes in the normalized maximum diameter and bounce height when three different concentrations of Fluo without and with surfactant droplets make contact with the surfaces of powdery mildew leaves.…”
Section: Resultsmentioning
confidence: 99%
“…13 The positively and negatively charged droplets stick firmly to the hydrophobic surface after contact. 14 New types of bounce-inhibiting materials have endlessly emerged, including covalent polymers, 15 supramolecular hydrogels, 16 and biological extracts, 17 which can all effectively inhibit the bouncing of droplets on hydrophobic surfaces. However, this situation is slightly different from agricultural applications and does not take into account the effects of combining these substances with pesticides, which are not yet known.…”
Section: ■ Introductionmentioning
confidence: 99%
“…It should be noted that nowadays there are typically two ways to tackle with the challenge of pesticide overuse. One is to reduce droplet splashing during pesticide spraying and strengthen the adhesion of pesticides to leaves after pesticide spraying; [ 20 , 22 , 23 , 74 , 75 ] the other is to control the pesticide release into a slow long‐term course. [ 29 , 78 , 79 ] As the present work proposes a simple, environmentally friendly and efficient method that combines the inhibition of droplet rebound with the enhancement of the interaction between pesticide and leaf surface and puts it into practice, the study to control pesticide release by such a system would be reported in the future.…”
Section: Discussionmentioning
confidence: 99%
“…The enhancement of pesticide drop retention is co‐contributed from two aspects, including 1) the droplet deposition and 2) pesticide adhesion to resist rainfall erosion. For example, the use of synthetic polymers, [ 9 , 18 , 22 ] surfactants, [ 19 , 20 , 21 , 22 , 69 , 70 , 71 ] charged droplets, [ 23 , 24 , 25 , 26 ] TiO 2 hydrophilic nanoparticles, [ 72 ] Folate/Zinc supramolecular hydrogels, [ 73 ] or nanofibers assembled from natural glycyrrhizic acid [ 74 ] could enhance 1) on the hydrophobic or superhydrophobic surfaces, while the use of nanocarriers such as high energy electron beam (HEEB)‐modified attapulgite aggregates, [ 27 , 28 ] plant ash, [ 75 ] polydopamine nanoparticles, [ 29 ] or phosphorylated zein (P‐zein) [ 30 ] enhances 2). Although trimeric surfactant [ 31 ] and castor oil‐based cationic/anionic polyurethane dispersions (WPU) [ 32 ] were used to increase droplet deposition while immobilizing pesticides have been reported, they are not ideal systems for pesticides retention due to their complex synthesis processes and low fixation efficiency.…”
Section: Introductionmentioning
confidence: 99%